f⁻¹(x) stands for the invers of function f(x). The inverse of f(x) is equal to x. We need to solve for x.
solve for x
f(x) = 2x + 2
2x + 2 = f(x)
2x = f(x) - 2
x =
![(f(x)-2)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8xkqyej2vytq3inqpa0619cvdky7ddbv2q.png)
f⁻¹(x) =
![(x-2)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9dx75k67tiq5dceteqyl8vqs9z5ghpka2r.png)
Determine the value of f⁻¹(x) when x = 4
f⁻¹(x) =
![(x-2)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9dx75k67tiq5dceteqyl8vqs9z5ghpka2r.png)
f⁻¹(4) =
![(4-2)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/t1p5jkxycpwd44476d6zpinjditu5bit5l.png)
f⁻¹(4) =
![(2)/(2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/8n2ec1wkcnnncof321t7vjl05twugapm8q.png)
f⁻¹(4) = 1
When x = 4, the value of f⁻¹(x) is equal to 1